TVET governance : steering collective action - Loveder, Phil [Verfasser] (UNESCO-UNEVOC International Centre for Technical and Vocational Education and Training, 2021)
"This volume is written with the macrolevel or system-level stakeholder in mind. Macro level stakeholders can be any number of bodies with a mandate for collective action in TVET. This primarily covers ministries and statutory bodies with legally assigned duties in the governance of TVET. Policy and operational managers interested in understanding some of the challenges and opportunities of introducing NQCs into TVET systems are most likely to benefit from the findings in this volume, but readers are encouraged to explore the other two volumes for additional insights: ‘TVET advocacy: ensuring multistakeholder participation’ targets meso-level stakeholders, while ‘TVET delivery: providing innovative solutions’ focuses on micro-level stakeholders.." (Publisher's abstract ; BIBB-Doku)
Keywords: I 1 Internationale Berufsbildung; G 1.2.3 Qualifikationsentwicklungen; 370; Berufsbildung; Internationale Zusammenarbeit; Bildungseinrichtung; Berufsbildungspolitik; UNEVOC; Qualifikationsentwicklung; Kompetenzentwicklung